Value of the individual components subject training gymnasts according to the survey of coaches with different skills - N. O. Andreeva (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : assess the significance of the individual components subject training gymnasts according to the survey of coaches with different skills. Material : two groups of coaches with different qualifications (n = 40). The first group of coaches -, experience from 1 to 10 years (n = 20); the second group - work experience from 11 to 25 years (n = 20). Gymnasts preliminary stage of basic training. Coaches are asked to answer 15 questions. Results : the content of questioning coaches gymnastics shows the relevance of the basic problems of technical training of young gymnasts (throwing and catching objects). The most difficult exercises in the training and improvement are throws and catches the ball (coefficient of concordance W = 0,814). The necessity of the development and use of new techniques for analyzing sports equipment exercises with the ball, learning and improving them. Conclusions : basic technical training and preparedness of gymnasts to perform exercises with objects represent a problem that is solved enough in theory and practice gymnastics.